Functional Outcome of Galezzi Fracture Dislocation in Adults Treated With Dynamic Compression Plate and Kirschner Wire - KC, Dipendra; Shrestha, Dinesh Kumar; Karki, Prateek; Shrestha, Sabin; Yogi, Sushil; Giri, Sagar (Journal of Nepalgunj Medical College, 2020)
Introduction: Galeazzi fracture-dislocation is a complex traumatic disruption of the distal radioulnar joint (DRUJ) that is associated with lower shaft radius fracture. Galeazzi fractures are extremely unstable, and the results of nonsurgical treatment are uniformly unsatisfactory. Galeazzi fractures managed with closed modalities have unsatisfactory clinical results in most of the patients in published literature so open reduction and internal fixation with plating is the standard treatment for this fracture.Aims: The aim of this study was to evaluate the functional outcome of Galeazzi fracture dislocation.Methods: This prospective study was conducted in the Department of Orthopedics at Nepalgunj Medical College Teaching Hospital Kohalpur, from April 2016 to March 2019.  It included 35 patients of age group 19 to 49. All of the fractures in this study were treated by open reduction and internal fixation (ORIF) with 3.5 mm narrow dynamic compression plate (DCP) and cortical screws via Henrys anterior approach and distal radioulnar joint (DRUJ) stabilization was done with 1 Kirschner wire (K-wire) inserted parallel to the wrist joint. Patients were observed at 6, 10, 16 and 24 weeks and 52 weeks both radiographically and clinically.Results: In this study of 35 patients, 24 (68.57%) were males and 11 (31.43%) were females with the age range of 19 to 49 years and mean age of 35 and standard deviation (SD) of ±1.5 years. Majority of fractures were observed between 31 to 40 years of age. Most of the injuries were due to fall injury 51.42%. The average duration from time of injury to surgery was 5 days and bone grafting was not needed in any cases. The average time period for union was about 16 weeks. The most common complication seen in this study was stiffness of wrist (11.42%). Twenty four patients (68.57%) had good result, 10 patients (28.57%) had fair result and one patient (2.86%) had poor result in DASH score at final follow-up.Conclusion: Open reduction and internal fixation with plating and stabilization of distal radioulnar joint with K wire yields good to fair outcome on Disabilities of Arm, Shoulder and Hand Score.